MRNA Transfection into CHO‐Cells Reveals Production Bottlenecks. Issue 2 (17th September 2019) - Coats, Michael T.; Bydlinski, Nina; Maresch, Daniel; Diendorfer, Andreas; Klanert, Gerald; Borth, Nicole
Abstract: Obtaining highly productive Chinese hamster ovary (CHO)‐cell clones for the production of therapeutic proteins relies on multiple time‐consuming selection steps. Several CHO‐cell strains with high degrees of genomic and epigenetic variation are available. Each harbor potential advantages and disadvantages for any given product, particularly those considered difficult to express. A simple test system to quickly assess compatibility of cell line and product may therefore prove useful. Transient plasmid transfection falls short of the specific productivities of stable producer cells, making it unsuitable for the elucidation of high specific productivity bottlenecks. The aim of the study is to reach specific productivities approaching those of industrial production cell lines by transfection of in vitro transcribed mRNA. The system is characterized with respect to transfection efficacy (by quantitative PCR) and protein production (by flow cytometry and biolayer interferometry). Fluorescence of intracellular eGFP saturates at higher amounts of mRNA per cell, while the amount of secreted and intracellular EPO‐Fc remain linearly correlated to the amount of mRNA taken up. Nevertheless, MS shows a severe reduction in N‐glycosylation quality. This method allows for rapid elucidation of bottlenecks that would otherwise remain undetected until later during cell line development, giving insight into suitable strategies for preemptive targeted metabolic engineering and host cell line optimization. Abstract : Cell line development for the production of biotherapeutics is a time‐consuming process, with the host cell‐line having a high influence on the resulting product quality. Dose‐dependent transfection of in vitro transcribed mRNA into CHO‐K1 host cells reveals bottlenecks in protein‐synthesis and posttranslational modifications. The presented method allows the researcher to subject any host cell‐line of choice to a high specific productivity, allowing for a rapid screen of host cell to product compatibility, and insight into bottlenecks that may appear later on during cell line development.